Cervical cancer in women of the Far Eastern Federal District (morbidity and mortality) - T. N. Chimitdorzhieva (ABV-press, 2020)
Objective: to analyze the incidence and mortality of cervical cancer in the Far Eastern Federal district (FEFD) in 2008-2018.Materials and methods. To assess the incidence and mortality of cervical cancer among women residing in FEFD, we used annual reports of P. Hertzen Moscow Oncology Research Institute - branch of the National Medical Research Radiology Center, Ministry of Health of Russia, for 2008-2018. We evaluated extensive and standardized parameters (per 100,000 population; 0/0000) calculated using the direct method (world standard). The prognosis was based on the 11-year dynamics of the incidence and mortality; regression coefficients were calculated using the standard method. Data analysis was performed using the Statistica 8.0 and Microsoft Excel 2003 software with a significance level of p £0.05. We evaluated the incidence and mortality of cervical cancer among women of FEFD registered between 2008 and 2018: during a 5-year period (2008-2012) and a 6-year period (2013-2018) for the whole region, as well as for individual administrative territories.Results. We found that the incidence of cervical cancer in FEFD was higher than its national incidence (14.3 ± 0.10/0000) and was steadily increasing in all administrative centers of FEFD. The highest incidence was observed in Zabaikalsky Krai (32.6 ± 1.90/0000, which is 2.3 times higher than national incidence). The quickest growth of cervical cancer incidence was registered in the Republic of Buryatia (69.6 %; growth rate 6.5 % (p £0.05)). This territory was also characterized by the highest mortality (11.4 ± 0.50/0000, which is 2.2 times higher than national mortality (5.3 ± 0.20/0000) (p <0.01)).Conclusions. The analysis of the cervical cancer incidence and mortality in FEFD demonstrated their steady increase, which makes the issues of disease prevention and early diagnosis highly relevant and indicates a clear need to activate vaccination and screening programs.